KEDUDUKAN HUKUM PERJANJIAN IKATAN DINAS DALAM UNDANG-UNDANG KETENAGAKERJAAN - Mawar Sitohang (Fakultas Hukum Universitas Kristen Indonesia, 2019)
Abstrak The implementation of Service Work Agreements in practice is frequently interpreted to mean in many form of various interpretations when a disputes occur between employers and employees. Some interpret disputes regarding service work agreements including industrial relations disputes, and some interpret them as general civil disputes based on agreements. This writing will examine how the actual position of official service work agreements in civil law both in terms of contract law and labor law. The method used is a normative description with a case approach. The conclusion is that labor law has firmly regulated focus on certain time employment agreements and non-specified time employment agreements. While the service work agreement is clearly included in the general civil agreement law. Keywords: service agreement agreement, service agreement agreement dispute settlement